Transforming Education with Virtual Reality - Malik, Reena; Sharma, Ambuj; Chaudhary, Prashant (John Wiley & Sons, 2024)
Virtual reality (VR) technology has thoroughly transformed education by providing engaging and immersive ways for students to experience their education and by offering visual learning, creative development, etc., to enhance their studies. Moreover, with increasing accessibility, both students and educators can utilize it for effective teaching and learning. By embracing this VR-related technology, teachers can transform traditional classrooms into lively ones. Businesses can also leverage VR for skilling, up-skilling, and re-skilling.